PENGUKURAN RESIKO Teknologi Informasi (TI) DENGAN METODE OCTAVE-S - Gui, Anderes; Gondodiyoto, Sanyoto; Timotius, Irvan (Bina Nusantara University, 2008)
Article presented a measurement of Information Technology (IT) risk levels and identify security practices whichwere suitable in the risk overcoming, as noted in PTNL. Company was also expected to be more alert to the risk impactsof information technology which might occur in PTNL. Analytical method used was OCTAVE-S method. This method wasused in a risk measurement of information technology risk, with some steps which had important roles in searching for themeasurement results effectively and efficiently, which were applied in PTNL. The results which will be achieved were to giveoverall results of risk measurement occurred at the company, either the plus or minus, and provide recommendations whichare expected to solve and correct the minus or problems which occurred in PTNL. Conclusion states that the risk measurementof information technology performed in PTNI has successfully minimized the risks that can threaten the company’s security.Keywords: measurement, risk, Information Technology (IT), OCTAVE-S method